A single patient with both pulmonary tuberculosis and borderline leprosy, accompanied by a Type-II leprosy reaction - Madhav Mahawar; Keertivardhan Kulkarni; Shreeshail Anjutagi; B. Likhitha (BLDE University Journal of Health Sciences)
Leprosy and tuberculosis (TB) are endemic to India, yet their coinfection is rare. This case report presents a 24-year-old female with lepromatous leprosy who developed pulmonary TB while undergoing multidrug therapy. The patient exhibited respiratory symptoms and was diagnosed with active TB following imaging and sputum tests. Despite the lack of comorbidities, she had been treated with corticosteroids for Type 2 lepra reactions, potentially increasing her TB susceptibility. This highlights the need for vigilant screening for TB in leprosy patients receiving immunosuppressive therapy to enable early diagnosis and appropriate management.